The moon cycle effect on the activity patterns of ocelots and their prey - Pratas-Santiago, Luís Pedro; Gonçalves, André Luis Sousa; Maia Soares, A. M.V. da; Spironello, Wilson Roberto (Journal of Zoology, 2016)
The time of the activity may be changed throughout the circadian cycle to increase the fitness of species and allow their co-existence. The goal of this paper was to test whether the activity patterns of ocelots Leopardus pardalis are synchronized with those of their potential prey, and assess the effect of the moon cycle on this predator–prey relationship, through camera-trapping. Activity levels of ocelots and potential prey have been assessed across circadian and moon cycles and the temporal overlap between them was calculated for each moon phase. Ocelots have shown to be nocturnal and the number of their records has been constant across the moon cycle, and their activity patterns overlapped those of their nocturnal prey significantly more than remaining species', during full moon. These findings suggest that ocelots switch the type of prey (diurnal or nocturnal) they hunt in different moon phases and display higher hunting success in full moon nights. © 2016 The Zoological Society of London
Keywords: Activity Pattern; Coexistence; Felid; Fitness; Lunar Phase; Nocturnal Activity; Predator-prey Interaction; Temporal Cycle; Leopardus Pardalis